Determinants of Islamic E-Wallet Adoption Among University Students: Evidence from Digital Islamic Literacy and Social Influence - Ainun; Nur Fitri Hidayanti; Zaenafi Ariani; Magomed Tazhdinov (International Journal of Islamic Business and Economics (IJIBEC), 2025)
This study aims to analyze the relationship between Islamic digital literacy and social influence on the acceptance of Islamic digital wallets among students, as well as to examine the role of Islamic digital literacy as a factor that strengthens this relationship. The method used is quantitative with a survey approach of 54 Muhammadiyah University Mataram students selected at random. The instrument used was a five-point Likert questionnaire, with data analysis using descriptive tests, normality tests, multiple linear regression, and ANOVA through IBM SPSS. The results of the study indicate that Islamic digital literacy (X1) and social influence (X2) have a positive and significant effect on students' interest in using Islamic digital wallets (Y1), with an R² value of 0.651 and significance p < 0.001, and the largest contribution came from social influence (β = 0.443) compared to Islamic digital literacy (β = 0.434). These findings confirm that Islamic digital literacy and social influence simultaneously increase the acceptance of sharia-based financial services. Practically, the research results provide a basis for strengthening strategies for education and promotion of digital Islamic financial literacy, as well as the integration of a social influence-based approach to expand Islamic financial inclusion among the younger generation.